Strikes and Holdouts in Wage Bargaining: Theory and Data - Cramton, Peter C.; Tracy, Joseph S. (American Economic Review, 1992)
We develop a private-information model of union contract negotiations in which disputes signal a firm's willingness to pay. Previous models have assumed that all labor disputes take the form of a strike. Yet a prominent feature of U.S. collective bargaining is the holdout: negotiations often continue without a strike after the contract has expired. Production continues with workers paid according to the expired contract. We analyze the union's decision to strike or hold out and highlight its importance to strike activity. Strikes are more likely to occur after a drop in the real wage or a decline in unemployment.